Optimizing the extraction of secondary metabolites from Ulva lactuca using response surface methodology - Shukor, Muhammad Idham; Darnis, Deny Susanti; Aminudin, Nurul Iman; Mohammad Noor, Normawaty; Bakhtiar, M. Taher (2023)
The various extraction of secondary metabolites from various biomass is a recent rising interest in an attempt to find natural alternatives for the chemical compounds cosmetical and pharmaceuticals industries. These extraction methods can be further modified with several factors to suit specific requirements. The present work aimed to screen and optimized the extraction of secondary metabolites from different drying methods (sun-dried, air-dried, oven-dried, and freeze-dried) of Ulva lactuca using orbital shaker-assisted extraction, conventional solvent extraction, and ultrasonic-assisted extraction. In this respect, a screening procedure using a Two-Level factorial design was employed to assess the effect of three different factors at two levels and their interactions on the concentration of secondary metabolites from U. lactuca. The studied factors were solute-to-solvent ratio, time of extraction, and temperature. The two levels chosen for extraction were solute-to-solvent ratio (1:20 to 1:50 g/mL), extraction time (20 to 60 mins), and temperature (30 to 70°C). N-hexane:acetone: methanol (2:1:1) was used as an extracting solvent. β-Carotene, fucoxanthin, and quercetin concentrations were set as responses for optimum output. Further analysis for optimization was conducted by using Central Composite Design. The results showed that all factors are dominant and significantly affect the extraction process. The optimum extraction parameters were solute-to-solvent ratio (1:31, 1:52, and 1:50 g/mL), extraction time (84, 87, and 75 mins), and temperature (32, 34, and 35°C) for β-carotene, fucoxanthin, and quercetin, respectively. Under these conditions, the maximum value for β-carotene was calculated as 0.168891 mg/g, fucoxanthin (0.1067 mg/g) and quercetin showed a maximum calculated value of 0.09733 mg/g with the desirability of 0.98178, 0.988 and 0.994, respectively. The present study indicates that U. lactuca can be used as a source of carotenoids and phenolic compounds that can be applied in cosmetical and pharmaceutical products as optimum extraction conditions.